The Role of Physical Activity in Enhancing Mental Health among Adults Facing - Hasbullah, Bahmid (Bulletin of Counseling and Psychotherapy, 2024)
Exercise has many physical benefits, including stress reduction. Individuals who exercise regularly tend to appear more relaxed and cheerful, making them more resilient to both physical and emotional stress. This is particularly relevant for medical students who may experience stress due to changes in learning styles from middle school to higher education. The purpose of this study was to investigate the relationship between exercise habits and stress levels in the community of XYZ area in Ambon. This study employed a cross-sectional design and utilized two basic instruments: the Exercise Habits Questionnaire and the DASS-42 Questionnaire. A total of 96 respondents were sampled and analyzed using the Chi Square test. The results showed that 38 respondents (39.6%) exercised regularly, while 58 respondents (60.4%) did not. Fifty-seven respondents (59.4%) reported a normal stress level, while 9 (9.4%) reported a light level, 13 (13.5%) reported a moderate level, 12 (12.5%) reported a severe level, and 5 (5.2%) reported a very severe level. The Chi Square test yielded a p-value of 0.144. The research findings indicate that there is no significant correlation (p=0.144) between exercise habits and stress levels among the people of XYZ Village in Ambon City.